Corona Discharges on von Reichenbach’s Terrellae? - Van der Sluijs, Marinus (Journal of Scientific Exploration, 2022)
In the 1840s, extensive experimentation led von Reichenbach to postulate an ‘Odic force’ associated with ‘Odic light’ or ‘magnet light’, of which the polar aurora would be an example in space. The physical nature of the visible phenomena reported by his assistants during the experiments has never been satisfactorily identified. It is argued that ‘Od’ compares to plasma or ionised gas, while at least a subset of the investigations, conducted on terrellae, represented the first experimental work on corona discharges. Accordingly, the glows on the terrellae cannot be directly compared to the aurora.